NANOPARTICLE: AS TARGETED DRUG DELIVERY SYSTEM FOR DEPRESSION - Deore, Swati; Shahi, S. R.; Dabir, Priyanka (International Journal of Current Pharmaceutical Research, 2016)
Nanoparticles (NP) are defined as particles with a diameter smaller than 100 nm, are increasingly used in different applications, including drug carrier systems and to pass organ barriers such as the blood-brain barrier. Particulate systems like nanoparticles have been used as a physical approach to alter and improve the pharmacokinetic and pharmacodynamic properties of various types of drug molecules. Different methods containing various polymers are used for formulation of nanoparticle to increase therapeutic benefit, while minimizing side effect for drug delivery research. While benefits of nanotechnology are widely publicised, the discussion of the potential effects of their widespread use in the consumer and industrial products are just beginning to emerge. This review provides comprehensive analysis of data available on health effects of nanomaterials.